High-Efficiency and Wide-Dynamic-Range Rectifier Based on Power Reflection for Wireless Power Transfer in Sensor Networks - Zhen Yue; Xin Xu; Si Hui Wu; Xian Qi Lin (IEEE Journal of Microwaves)
This paper proposes an efficient and wide dynamic range rectifier based on power reflection structure. The rectifier consists of a branch-line coupler and two sub-rectifiers operating at different input power levels. The branch-line coupler is used as power reflection structure. Due to the electromagnetic symmetry of the branch-line coupler and the non-linear characteristics of the rectifier, the power reflection structure can reflect mismatched energy caused by load variations or input power fluctuations back into the sub-rectifier, which can improve the reflection coefficient of the rectifier. For validation in different application scenarios, two rectifiers operating at 5.8 GHz were designed, fabricated, and characterized. For the proposed rectifier I (with load resistances RL1 = 750Ω and RL2 = 300Ω), the measured PCE maintains exceeding 50% when the input power ranges from 8 to 29.2 dBm, and the peak PCE is 68.01% at 18 dBm input power. While for rectifier II (with load resistances RL3 = 800Ω and RL4 = 300Ω), the measured PCE remains over 50% with input power from −1.2 to 28.8 dBm, and the peak PCE is 68.51% at 15 dBm input power. Theoretical analysis and performance comparison are carried out that excellent performance of proposed rectifiers in extending the input power range, which can widely apply in WPT system.